2010
DOI: 10.1371/journal.pone.0009771
|View full text |Cite
|
Sign up to set email alerts
|

3D Analysis of the TCR/pMHCII Complex Formation in Monkeys Vaccinated with the First Peptide Inducing Sterilizing Immunity against Human Malaria

Abstract: T-cell receptor gene rearrangements were studied in Aotus monkeys developing high antibody titers and sterilizing immunity against the Plasmodium falciparum malaria parasite upon vaccination with the modified synthetic peptide 24112, which was identified in the Merozoite Surface Protein 2 (MSP-2) and is known to bind to HLA-DRβ1*0403 molecules with high capacity. Spectratyping analysis showed a preferential usage of Vβ12 and Vβ6 TCR gene families in 67% of HLA-DRβ1*0403-like genotyped monkeys. Docking of pepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 46 publications
2
27
0
Order By: Relevance
“…Such minimal subunit-based mHABPs must fulfil set physicochemical and topochemical rules (previously described) to properly display a perfect fitting into MHCII-pep-TCR complex [12].…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…Such minimal subunit-based mHABPs must fulfil set physicochemical and topochemical rules (previously described) to properly display a perfect fitting into MHCII-pep-TCR complex [12].…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…Such observations were also made for P4, P6 and P9, meaning that the MHC II--peptide interaction, and therefore the immune response, was dependent on the stereo-electron characteristics of residues forming genetically determined pockets [95,96]. For instance, HLADRb1*PBR P1 was formed by hydrophobic or aromatic amino acids, was deep and hydrophobic so that it preferred aromatic residues such as Trp, Phe and Tyr with which it established resonant B-B bonds [95][96][97][98]. However, when this pocket had the dimorphic variant Gb86V, the physicochemical differences between amino acids induced steric hindrance obstructing the fit of large aromatic residues like Trp and Tyr, but allowed large apolar residues, such as Leu, Ile, Met and Val and even Phe.…”
Section: Mhabp Structure--function Relationshipmentioning
confidence: 78%
“…Moreover, mixtures formed by Spz-and Mrzderived mHABPs binding to different HLA-DRb1 genetic backgrounds and having such side-chain orientation induced sterile immunity against very different functionally relevant targets or, as we have called them, the malaria parasite's Achilles' heel [81]. The binding--structure--function relationship was taken into account when developing the IMPIPS concept, requiring the determination of stereo-electron and topochemical characteristics essential for MHC--IMPIPS--TCR complex formation [11,86,91,98,102,103]. Figure 5 outlines the aforementioned practical approach, using malaria as model, for developing a logical and rational methodology, based on physicochemical principles, which could be followed when developing vaccines against different diseases which, even in the twenty-first century, continue to scourge humankind.…”
Section: Expert Opinionmentioning
confidence: 99%
“…The amino acids have been written using one-letter code when they have been derived from the modified peptide and in three-letter code if they have been HLADRb1* chain-derived. Replacements were made in this molecule's sequence based on the differences found in the protein-binding region (PBR), as reported in previous studies (Suarez et al 2006;Patarroyo et al 2010a). The amino acids replaced in the HLA-DRb1*0403 molecule were Argb71Lys, Glub74Ala and Valb86Gly.…”
Section: Molecular Modellingmentioning
confidence: 99%
“…Studies by Suarez et al (2006) and Patarroyo et al (2010b) have shown that the HLA-DRb1*0403-like allele had higher frequency in the Aotus monkey population being studied, since immunisation and protection studies with these peptides were performed with a sequence from the Aotus HLA-DRb1*0403 chain when using this non-human primate model (Suarez et al 2006;Patarroyo et al 2010a). It was thus decided to carry out molecular modelling analysis, making the corresponding b-chain replacements (residues highlighted in black in the turquoise ribbon shown in Fig.…”
Section: Molecular Modellingmentioning
confidence: 99%